Liquid Separations with Membranes An Introduction to Barrier Interference - Böddeker, Karl W. (Springer International Publishing, 2018)
This book presents a self-consistent approach to separations of liquids with membranes, contrasting equilibrium separations with the rate-controlling effects of barrier interference on mass transfer. Unlike equilibrium separations, which depend on the thermodynamic condition of the fluid mixtures alone, barrier separations additionally are subject to specific interactions of the mixture components with the barrier. While the thermodynamics of fluid mixtures is predictable and open to adjustment, barrier interference adds another dimension to the repertoire of separation effects. Exploiting barrier interference is the challenge of membrane separation science and technology. This book is about the principles behind. This second edition incorporates the remarkable new developments especially in the field of hydrophobicity of surfaces and closely connected membrane distillation. Additionally, the new edition includes a chapter on Electrodialysis and its potential for energy efficient seawater desalination.